Real-time monitoring of etoposide prodrug activated by hydrogen peroxide with improved safety. Issue 47 (13th November 2019) - Zhu, Jiawen; Chen, Jingting; Song, Dongmei; Zhang, Wenda; Guo, Jianpeng; Cai, Guiping; Ren, Yuhao; Wan, Chengying; Kong, Lingyi; Yu, Wenying
Abstract : A novel H2 O2 sensitive prodrug designed for selectively releasing etoposide in cancer cells with fluorescence monitoring and improved safety. Abstract : Etoposide is one of the most used first-line chemotherapeutic drugs. However, its application is still limited by its side effects. Herein, we designed a novel H2 O2 sensitive prodrug 6YT for selectively releasing the anti-cancer drug etoposide in cancer cells. In this paper, etoposide and a hydrogen peroxide (H2 O2 ) sensitive aryl borate ester group were linked by a fluorescent coumarin and finally the prodrug 6YT was generated. The fluorescence of coumarin was quenched before the connected aryl borate ester group was cleaved by H2 O2 . However, in the high level H2 O2 environment of the tumor, the fluorescence could be activated simultaneously with the release of etoposide, and the drug release state of the prodrug was monitored real-time. With the support of 6YT, we obtained direct and visual evidence of etoposide release in a high H2 O2 environment both in cells and zebrafish. The prodrug 6YT was also verified with comparable activity and improved safety with etoposide both in cells and in a mouse model. As a safe and effective prodrug, 6YT is expected to be one of the promising candidates in chemotherapy against cancer.